Phlorotannins suppress adipogenesis in pre-adipocytes while enhancing osteoblastogenesis in pre-osteoblasts - Karadeniz, Fatih; Ahn, Byul-Nim; Kim, Jung-Ae; Seo, Youngwan; Jang, Mi-Soon; Nam, Ki-Ho; Kim, Mihyang; Lee, Sang-Hyeon; Kong, Chang-Suk (Archives of pharmacal research, 2015)
Osteoporosis, a prevalent bone disease in an aging population, is considered to be closely related to osteoblastogenesis and adipogenesis. As a part of an ongoing trend to develop natural substances that attenuate osteoporotic conditions, edible brown algae E. cava and its bioactive constituents were tested for their effects on adipogenic differentiation in 3T3-L1 fibroblasts and osteoblast differentiation in MC3T3-E1 pre-osteoblasts. Following an activity-based isolation, three phlorotannin derivatives, triphlorethol-A (1), eckol (2) and dieckol (3), were isolated. Anti-adipogenesis effect of phlorotannins at the concentration of 20 µM was observed by reduced lipid accumulation and the suppressed expression of adipogenic differentiation markers. In addition, isolated phlorotannins successfully enhanced the osteoblast differentiation as indicated by increased alkaline phosphatase activity along with raised levels of osteoblastogenesis indicators and intracellular calcification at the concentration of 20 µM. In conclusion, E. cava is suggested as a source for functional food ingredients, especially phlorotannin derivatives that can be utilized for extenuating osteoporosis and obesity.